Probe design for exploiting gene encoding pectinesterase from dna metagenome data of bacteria in goat rumen and co-expression of gpecs1 gen with chaperone pg-kje8 in Escherichia coli - Hoang Viet, Nguyen Khanh; Huyen, Do Thi; Lam, Le Tung; Lan, Phung Thi; Nguyet, Phung Thu; Tien, Nguyen Thuy; Hai, Truong Nam (Academia Journal of Biology, 2018)
This article introduces the steps of constructing and using probe to exploit the gene encoding pectinesterase from metagenome DNA sequencing data by next generation gene sequencing tools. Probe was used to exploit and select the gene encoding for pectinesterase from the metagenome DNA sequences of bacteria in goat rumen and thereby select a sequence to express in E. coli. According to the CAZy classification system, pectinesterase belongs to the family of carbohydrates esterases CE8 is an enzyme that has many applications in the food processing industry, environmental treatment, animal feed processing and medicine. As the results, 3 sequences of CE8 was retrieved from CAZy database and one probe was designed, this probe length was 367 amino acids contained all the conserved amino acid residues: 200 conserved residues in all sequence, 72 residues similar in almost sequences and residues conserved in many sequences and homologus; choosed highest alkalinity index. Using the probe designed, we filtered four coding sequences for pectinesterase from metagenome DNA sequencing data of bacteria in goat rumen. Spatial structure estimation with Phyre2 has only one sequencing (code 46301) with 100% sequence identity and 90% query coverage with pectinesterase. A artificial gene were synthesized and inserted into the vector pET22b (+) at the NcoI, XhoI to co-express with chaperone pG-KJE8 in E. coli. The recombinant pectinesterase enzyme is expressed in soluble form and has a pectin substrate biodegradation activity. The results demonstrate that using probe for gene extraction is feasible.